2015
DOI: 10.1097/mpg.0000000000000696
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Youth With Crohn Disease

Abstract: Objectives Health-related quality of life (HRQOL) is an important, but understudied construct in pediatric IBD. Family-level predictors of HRQOL have been understudied as are the mechanisms through which disease activity impacts HRQOL. The current study examines the relationship between a family-level factor (parenting stress) and HRQOL in youth with Crohn's disease. Parenting stress is examined as a mechanism through with disease activity impacts HRQOL. Methods 99 adolescents with Crohn's disease and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 41 publications
(60 reference statements)
5
31
1
3
Order By: Relevance
“…139 A multicenter observational study of 99 adolescents with Crohn's disease concluded that disease severity increased parental stress and affected the patient's QOL. 140 A multidisciplinary approach, coordinated to occur during the same visit, is the optimal approach for patients tion. For this reason, serological screening for immunity to Epstein-Barr virus should be considered at diagnosis of IBD to guide the decision making process for treatment and to increase watchfulness in case of a future primary infection.…”
Section: Anemiamentioning
confidence: 99%
“…139 A multicenter observational study of 99 adolescents with Crohn's disease concluded that disease severity increased parental stress and affected the patient's QOL. 140 A multidisciplinary approach, coordinated to occur during the same visit, is the optimal approach for patients tion. For this reason, serological screening for immunity to Epstein-Barr virus should be considered at diagnosis of IBD to guide the decision making process for treatment and to increase watchfulness in case of a future primary infection.…”
Section: Anemiamentioning
confidence: 99%
“…Die Krankheitsaktivität wurde mehrfach als signifikanter Einflussfaktor bezogen auf die HRQoL eingestuft (z. B. Cohen's d (IMPACT-III Gesamtwert) = 0,72; p = 0,000 [15]) [16,22,26,28,30,31,32,33]. In diesem Zusammenhang ist auch zu erwähnen, dass die Krankheitsaktivität mit zunehmender Erkrankungsdauer sinkt (Pearson-Korrelation, r = 0,15; p = 0,05) und damit wiederum eine höhere HRQoL der Dimension Darmsymptome verknüpft ist.…”
Section: Gegenüberstellung Zweier Messinstrumenteunclassified
“…Auch die schulische Lebensqualität als Teildimension der HRQoL im PedsQL-Fragebogen ist bei Jugendlichen mit verheirateten Eltern deutlich höher (Mittelwert = 74,18 versus 57,50; p < 0,01) [35]. Zudem beeinflusst die Krankheitsaktivität die HRQoL über den Kofaktor elterlichen Stress [31]. Die HRQoL der an CED erkrankten Jugendlichen ist insbesondere bezogen auf die Teildimension der alltäglichen Aktivitäten, z.…”
Section: Ergebnisse Der Leitfadengestützten Experteninterviewsunclassified
See 1 more Smart Citation
“…The precise causes of Crohn's Disease are not well understood. It is a multifactorial disease including hereditary, genetics, and/or environmental factors inaddition to diet and stress may aggravate Crohn's Disease [8] .…”
Section: Pathogenesismentioning
confidence: 99%